Sejarah Berdirinya Masjid Cheng Ho di Kawasan Sriwijaya - Pratiwi, Astrid Putri; Maryamah, Maryamah; Jauhara, Jauhara; Mukjizat, Lailatul; Ayu, Salsyabina Puspita (Jurnal Dirosah Islamiyah, 2024)
The variety of cultures and religions of the population in Indonesia is because Indonesia has various ethnicities and races too. In Palembang, there are not only ethnic Malays, there are also people of Javanese, Indian, Acehnese and Chinese/Chinese descent. The ethnic Chinese in Palembang are thought to have come from Kuang Tung and Chyang Chou in mainland South China. This place is mostly Muslim, like the Yunnan region where Admiral Cheng Ho came from. In Palembang, there is also cultural acculturation where Palembang people marry ethnic Chinese. Ethnic Chinese are included in PITI. The founders of the Islamic Tauhid Faith Builders (PITI) are Halim (Yu), Ting and Sadiqin. The aim of PITI is to unite with Muslims, to become a gathering place for learning about the Islamic religion. This is why a mosque was founded. This mosque was built with ethnic Chinese patterns and was named the Al-Islam Muhammad Cheng Ho Mosque. The Muhammad Cheng Ho Mosque in the city of Palembang was founded by PITI or the Indonesian Chinese Islamic Association. This PITI institution regulates and maintains the Al Islam Muhammad Cheng Ho Mosque. This mosque has routine Islamic activities in the mosque, for example recitation, etc. The Cheng Ho Mosque is an interesting study because it takes the concept of cultural acculturation in the Palembang area. So what is the history and factors related to the Al-Islam Muhammad Cheng Ho Mosque in Palembang.